Effects of cholinesterase inhibitor medication on QTc interval in memory clinic patients - Lehtovaara, Joanna (My University, 2025)
Cholinesterase inhibitors (ChEIs) including donepezil, rivastigmine, and galantamine, are widely used and considered as the first-line therapy in the treatment of mild to moderate Alzheimer's disease (AD). In previous literature ChEIs have been associated with possible cardiac adverse effects including syncope, bradycardia, QT prolongation and Torsades de Pointes (TdP). However current clinical guidelines do not specifically address the issue of QT prolongation with ChEIs. This study aimed to evaluate the association between ChEI use and QTc interval prolongation in geriatric patients. This retrospective study analyzed data from first-time visitors at the geriatric memory clinic of Turku City Hospital in 2017 and 2019. Patients who were newly prescribed ChEIs and had available electrocardiogram (ECG) data were included (n=126, mean age 81.1 years, 56.3% women). QTc intervals before and during ChEI treatment were measured manually from ECGs. QTc prolongation was defined as ≥460 ms in women and ≥450 ms in men. Statistical comparisons were made using paired t-tests and McNemar tests. The results showed no statistically significant changes in QTc intervals before versus during ChEI use (mean QTc for all ChEIs: 419.7 ± 23.4 ms before and 421.5 ± 27.3 ms during treatment, P=0.34). Prolonged QTc occurred in 7.9% of patients before and 12.7% during ChEI use (P=0.21), but the difference was not statistically significant (P=0.21). In conclusion, this study found no statistically significant association between ChEI use and QTc prolongation. However, larger studies are recommended to further investigate the potential impact of ChEI medication on QT prolongation.
Keywords: Cholinergics, Alzheimer disease, Geriatrics, Drug Safety